Field reports form for submitting seasonal observations of Iowa birds, Beth Proescholdt, fall 1983 - Proescholdt, Bethet al (1983)
An annotated list of birds sighted by Beth Proescholdt and others. Includes a letter regarding a sighting of Tundra Swans. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1983. Epson - sheet feed